An inducible offense: carnivore morph tadpoles induced by tadpole carnivory. Issue 7 (4th March 2015) - Levis, Nicholas A.; de la Serna Buzón, Sofia; Pfennig, David W.
Abstract Phenotypic plasticity is commonplace, and plasticity theory predicts that organisms should often evolve mechanisms to detect and respond to environmental cues that accurately predict future environmental conditions. Here, we test this prediction in tadpoles of spadefoot toads, Spea multiplicata. These tadpoles develop into either an omnivore ecomorph, which is a dietary generalist, or a carnivore ecomorph, which specializes on anostracan shrimp and other tadpoles. We investigated a novel proximate cue – ingestion of Scaphiopus tadpoles – and its propensity to produce carnivores by rearing tadpoles on different diets. We found that diets containing tadpoles from the genus Scaphiopus produced more carnivores than diets without Scaphiopus tadpoles. We discuss why Scaphiopus tadpoles are an excellent food source and why it is therefore advantageous for S. multiplicata tadpoles to produce an inducible offense that allows them to better utilize this resource. In general, such inducible offenses provide an excellent setting for investigating the proximate and evolutionary basis of phenotypic plasticity.